Synthesis, characterization and corrosion resistance of electroless Ni-P and Ni-P-SiC coatings: a comparative study - Camargo León, Magali Karina (2010)
Electroless Ni-P coatings have been widely used due to their good combination of properties such as hardness, wear resistance and corrosion resistance. The addition of dispersed hard micro-particles into the Ni-P matrix has led to the development of composite coatings. Ni-P composite coatings exhibit an improved hardness and wear resistance properties; however, there is still a disagreement among researches on the corrosion behavior of composite Ni-P coatings. The present investigation involves the synthesis, characterization and a comparative study of the corrosion resistance in NaCl 3,5% of electroless Ni-P and Ni-P-SiC deposits obtained by either prepared or commercial electrolytic nickel/hypophosphite based baths. The characterization of deposits involved studies about morphology by SEM, chemical composition by energy-dispersive X-ray spectroscopy (EDX) and glow discharge optical emission spectroscopy (GDOS), microstructure by X-ray diffraction (XRD) and hardness. All deposits showed an amorphous micro-structure and high phosphorus content (10-14 wt%). Ni-P-SiC deposits showed an increased hardness (802 HV-815 HV) in comparison with Ni-P deposits (469 HV-626 HV). The techniques used to study the corrosion resistance in NaCl 3,5% were linear polarization resistance (LPR), Tafel plots and electrochemical impedance spectroscopy (EIS). These techniques agreed to show the better corrosion resistance of Ni-P-SiC coatings over the Ni-P coatings. This fact can be ascribed to the decrease in the effective metallic area available for corrosion. Ni-P-SiC deposits exhibited higher polarization resistance (Rp) values (103-66 kΩ.cm2) in comparison with Ni-P deposits (46-55 kΩ.cm2). Also, the corrosion current density values of Ni-P-SiC deposits (0,17-0,65 µA/cm2) were lower than Ni-P deposits (0,71-1,08 µA/cm2). Concerning to the mechanism by which the Ni-P and Ni-P-SiC become corroded, EIS experiments demonstrated that the corrosion process involved a charge transfer mechanism in all the cases. Tafel plots also corroborated this mechanism since of all deposits showed a Tafel behavior.